PENGEMBANGAN DAN PERANCANGAN PROSES PRODUKSI KECAP BERBAHAN BAKU KEDELAI KUNING LOKAL - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Local yellow soybean is rarely used as raw material for kecap (soy sauce) production. The aim of this research is to design a kecap production process using local yellow soybean as the raw material. Production wasstarted by cooking the local yellow soybean in dilute acid solution to adjust the pH to be 4.5. This condition was very important for fungal growth and to prevent a lot of colloid produced during cooking. Mixed culture starter of Asperaillus orvzae and Aspergilus soiae was used for koji fermentation. Moromi fermentation was tried by using 3 different methods. In the first method, fermentation was carried out as the ordinary kecap fermentation. In the second method, Pediococcus halofJhvluswas inoculated in the beginning of the moromi fermentation, and after 1.5 months, halophylic yeast was inoculated into the moromi mash. In the third method, fermentation was carried out as the second method, but after 1.5 months, moromi was filtered, and halophylic yeast wasinoculated for further fermentation until 3.5 months. Thefilter cake was fermented further by incubation in room temperature until the product has tauco flavor. The results indicated that the second method produced the best kecap flavor compared to the others. The filtration in the third method has benefit if the production will be conducted in an industrial scale, in order to have an easier material handling.